Getting to the heart of the matter: diagnostic tools and therapeutic approach to cardiac involvement in Behçet syndrome A Tunisian case series - A.S. Hammami; M. Jellazi; S. Arfa; S. Daada; K. Ben Hamda; A. Achour; S. Ouali (PAGEPress Publications, 2021)
The aim was to investigate the frequency and spectrum of cardiac involvement (CI) in patients with Behçet syndrome (BS) in the Tunisian context, and to assess the clinical and imaging features, treatment, and outcomes. We retrospectively retrieved the medical records of patients with CI among 220 BS patients admitted to the hospital internal medicine department between February 2006 and April 2019, who fulfilled the International Study Group diagnostic criteria for BS. Ten patients (8 men, 2 women) were eligible for the study. Mean age was 37.3 years. Three patients had 2 isolated episodes of cardiac BS. The different types of CI were coronary artery disease (5/10), intracardiac thrombus (4/10), pericarditis (1/10), myocarditis (1/10), and myocardial fibrosis (1/10). Five patients had associated vascular involvement (50%). Medical treatment was based on corticosteroids and colchicine in all patients (100%), anticoagulants in 8 (80%), and cyclophosphamide followed by azathioprine in 9 (90%). The clinical course was favorable in 9 patients; 1 patient died. CI remains an important feature of BS because of its association with increased risk of mortality and morbidity. Therefore, early screening and detection with imaging methods are paramount. Also, better cooperation between rheumatologists and cardiologists could improve outcomes.